The techno-economic aspects for the qualification of sustainable reconditioning and spheroidisation of Titanium Alloy (Ti6Al4V) powder for additive manufacturing - Dube, Tsepo Maqhetuka (Stellenbosch : Stellenbosch University, 2025)
Dube, T. M. 2025. The techno-economic aspects for the qualification of sustainable reconditioning and spheroidisation of Titanium Alloy (Ti6Al4V) powder for additive manufacturing. Unpublished doctoral dissertation. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/5759c187-a8c3-4f63-a8c0-99c5e4e61397